Electronic government and the information systems perspective : 5th International Conference, EGOVIS 2016, Porto, Portugal, September 5-8, 2016, Proceedings /: 5th International Conference, EGOVIS 2016, Porto, Portugal, September 5-8, 2016, Proceedings. (2016) - Unknown
No abstract available